A Tangentially Visible Fast Imaging System on EAST - 贾曼妮 杨清泉 钟方川 曾爱军 卢洪伟 舒双宝 (Plasma science & technology, 2015)
A tangentially visible imaging system has been developed on the Experimental Advanced Superconducting Tokamak（EAST） to record the full cross-section plasma visible radiation with speed up to 7500 frames per second at full resolution or much faster for a limited number of pixels.The edge localized mode（ELM） filaments during ELM eruptions in H-modes are captured.Using these pictures,the current in the filament is estimated.